PEMBAGIAN HARTA BERSAMA AKIBAT PERCERAIAN: STUDI KASUS DI PENGADILAN AGAMA BEKASI - ., Widowati; ., Suprihatin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2014)
The purpose of this research is to understand the process of implementation of the practice and meaning of the division of joint property of the Religious Court of Bekasi. The conclusion of this study are as follows: (1) Implementation of the Joint Distribution Assets through several stages, namely: a) the plaintiff made a claim; b) registration of the case by the desk clerk 1 to the register book; c) The plaintiffs to pay court costs as well specify the case number; d) the Chairman of the Religious Court Judge sets (PMH) as well as clerks and secretaries appoint a replacement clerk of the bailiff who will assist the judge in the trial; e) The judges set the day of the examination of the case is once ruled-the bailiff to call the parties; f) First Session: mediation stage and give answers lawsuit either orally or in a written, then deliver replik and closing argument; g) Defendants and plaintiffs submit evidence as witnesses, deed, and the oath. After verification of the defendant and the plaintiff a new panel of judges gave the verdict and its final conclusion. (2) treasure together in Law No. 1 1974 and Compilation of Islamic Law shows the constellation akultu process that produces the process of assimilation or fusion of two cultures. In this case, the process of acculturation and assimilation to the joint property appears easy occurs among Muslims, because basically in the treasures of the teachings of Islam are thinking about going on his property along with the term "shirkah" which has been recognized Islamic community